JARGON USED BY STYLISTS IN RABEL BEAUTY SALON GALUNGGUNG MALANG - ARDIYANTO, ARIN ANDHINI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Sociolinguistics, Jargon, Salon, Rabel Beauty Salon, StylistSociolinguistics is the study related to the language and society. In Sociolinguistics, we know the concept of jargon. Jargon is the certain language that is usually used by group of society. Jargon is a language variety contain a set of unique vocabulary that used by people who have same interest, class (social status), or same position in certain area, for instance in working area. This study uses theory of Yule (1996, p.245) defines Jargon is one of the key features to register in a certain group, which can be defined as technical vocabularies associated with a special activity or group. There are three research problems of this study: (1) What are the jargons used by stylist in Rabel beauty salon (2) What are the jargons used by stylist in Rabel beauty salon (3) What are the possible reasons of using those jargons by stylist in Rabel beauty salon. This study uses qualitative descriptive approach because the writer describes the jargon used by stylist in Rabel beauty salon, the meanings and also the possible reasons  of using those jargons.  As  the data,  the writer uses  the utterances which contain jargon when the stylists talk among each other. The result of the interview is also regarded as the supporting data. The writer finds the stylists in Rabel beauty salon use 19 jargons when they are providing salon’s treatment. They use jargon for certain reasons. First it is done keep their secret talk. Secret here means that their talk that do not want to be known by other people who do not belong to this community. Second, they use jargon  to  build  their  own  identity.  They  want  their  community has  different characteristic from the others. The writer suggests that, hopefully, the future researcher presents better research. First is for the next researchers are expected to explore and investigate some other phenomena of jargon happen in society in any speech community in order to add other types of jargons, so it will be found more various languages than before. Second, try to investigate other studies in some linguistics field such as pragmatics, syntaxes, and others. The last suggestion, hopefully the next researchers have a lot of other theories which are support their study and make the sources to be more various.